Biochemistry / Donald Voet; Judith G Voet - Voet, Donald
Accompanied by an integrated biochemical interactions CD, this text explains biochemical concepts while offering a unified presentation of life and its variation through evolution. It incorporates classical and current research to illustrate the historical source of much of our biochemical knowledge.